Some physical limitations in the performance of statistical multiple-input multiple-output RADARs - Migliore, M.D. (IET microwaves, antennas & propagation, 2008)
The objective of the study is to clarify some physical limitations in the performance of statistical RADAR systems using multiple antennas. In particular, it is shown that the performance of the recently proposed statistical multiple-input multiple-output (MIMO) RADAR is limited by the Number of Degrees of Freedom (NDF) of the scattered field. Furthermore, the true nature of statistical RADAR systems (single-input multiple-output, multiple-input single-output, MIMO) is not related to the number of transmitting/receiving antennas, but to the NDF of the scattered field exploited by the system.